Dampak Kompetensi dan Motivasi Kerja terhadap Kinerja Guru SMK Yadika 13 Tambun - Carolus Rizky Aditama Don Jose Wee; Novita Wahyu Setyawati; Indah Rizki Maulia (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine whether there is an impact of competency and work motivation on teacher performance at SMK Yadika 13 Tambun. The method used in this research is quantitative, the survey method is used to obtain primary data using questionnaires. The sampling technique used was a saturated sample with 40 respondents. The data analysis technique uses the t test and path analysis processed with SPSS 26. The results of the research show that in the t test (partial negative competency variables have no effect on performance with the calculation results obtained t-count (-2.125 < 2.02619) with a sig value of 0, 40 < 0.05. And the work motivation variable influences performance with the calculation results obtained by t-count (6.163 > 2.02619) with a sig value of 0.00 < 0.05. Based on the f test, simultaneously competence and work motivation have a significant effect on teacher performance.